Telaah Etnografi Mengenai Inkulturasi dan Akulturasi Sebagai Kearifan Lokal Etnis Baliem, Papua - Mawikere, Marde Christian Stenly; Hura, Sudiria (Tumou Tou, 2021)
This article is an ethnographic study of the Inculturation and Acculturation of the Baliem, as ethnic groups in the Land of Papua. The elements of inculturation under study consist of personality, leadership substance, ritual and communication, while the elements of acculturation studied consist of socio-cultural changes that occur in the Baliem community and their attitudes towards outside influences and other openness dynamics. This study shows that the Baliem ethnic group has a unique traditional cultural wealth and through the influence of the outside community has undergone socio-cultural changes which are supported by an open attitude to other communities. With such local wisdom, this study will contribute and stimulate learning, further research and a holistic community service and development approach, both spiritually, mentally and physically as well as dynamic contextually for the Baliem ethnic in Land of Papua.